2016
DOI: 10.1097/md.0000000000002674
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hashimoto Thyroiditis on Lymph Node Metastases in Unifocal and Multifocal Papillary Thyroid Carcinoma

Abstract: The purpose of this study was to investigate the risk factors for central and lateral neck lymph node metastases in papillary thyroid carcinoma (PTC) and multifocal papillary thyroid carcinoma (MPTC), particularly when associated with Hashimoto thyroiditis (HT).A retrospective analysis of 763 consecutive patients who underwent total thyroidectomy with bilateral central neck dissection in the First Affiliated Hospital, College of Medicine, Zhejiang University between October 2011 and October 2014 was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 43 publications
(42 reference statements)
4
49
2
5
Order By: Relevance
“…One case report showed that the appearance of TgAb may indicate the presence of metastatic LNs, but only in a limited number of subjects . These findings differed from those of a recent study by Zhu et al., which conducted a retrospective survey of 763 patients to examine the risk factors for central and lateral neck LN metastases in PTC associated with HT. A total of 277 (36.3%) patients with PTC and HT had a lower central LN metastasis rate than those with PTC and non‐HT, indicating a protective effect.…”
Section: Discussionmentioning
confidence: 80%
“…One case report showed that the appearance of TgAb may indicate the presence of metastatic LNs, but only in a limited number of subjects . These findings differed from those of a recent study by Zhu et al., which conducted a retrospective survey of 763 patients to examine the risk factors for central and lateral neck LN metastases in PTC associated with HT. A total of 277 (36.3%) patients with PTC and HT had a lower central LN metastasis rate than those with PTC and non‐HT, indicating a protective effect.…”
Section: Discussionmentioning
confidence: 80%
“…Частота діагносту-вання хронічного тиреоїдиту одночасно з ПК за об'єднаними даними літератури становить від 0,5 до 85 % [4,6,31,32]. Такі значні від-мінності, ймовірно, відображають як особли-вості патоморфологічного визначення, так і інтерпретації хронічного тиреоїдиту.…”
unclassified
“…Мишуніна, М.Д. Тронько заперечували думку, що тиреоїдит Хашимото не визначає, а затримує розвиток раку, бо ци-ркулюючі антитіла перешкоджають прогресії пухлин [26,32,38,61].…”
unclassified
See 1 more Smart Citation
“…Given its slow development and lack of clinical specificity, thyroid cancer can be hardly detected in the early period [2]. Currently, ultrasonic elastography has emerged as a new type of ultrasonoscopy technology with a wide array of applications [3]. In ultrasonic elastography, an external force is first exerted on tissues to cause distortion and deformation.…”
Section: Introductionmentioning
confidence: 99%